REDESAIN LOGO KAMPUNG COKLAT BLITAR SEBAGAI UPAYA PENGEMBANGAN DESTINASI WISATA BERBASIS NATURAL - Atho’illah, Muhammad; Budiardjo, Hardman; Yuan, Dhika (Jurnal Art Nouveau, 2017)
Blok Coklat Village is one of the natural-based tourist destinations that have facilities include; cocoa nurseries, cocoa plantations, cocoa bean dryers, chocolate processing plants, cooking classes, brown outlets, chocolate cafes, meeting rooms, fish therapies and outlets selling chocolate products.Blitar Coklat Village was developed by 48 (forty eight) farmer groups in Blitar district and incorporated as Cooperative named Gapoktan